Geochemistry of Beef-Penguin (PAT18-BP) peat core from Patagonia - Michael S Bunsen; Julie Loisel (PANGAEA, 2021)
Peatland core geochemistry and chronology data for site BP (Beef-Penguin unofficially). Age calculations made in Bacon, using calibration curve 7.0 with radiocarbon dates obtained from Lawrence Livermore National Labs (LLNL) Center for Accelerator Mass Spectrometry (CAMS).